Abdominal B-Cell Lymphoma Mimicking Ovarian Cancer - Dennis Jung; Lina Judit Schiestl; Simin Schadmand-Fischer; Arno Schad; Annette Hasenburg; Roxana Schwab (Diagnostics)
A 54-year-old patient presented in our clinic with pressure in the upper abdomen, dyspnea and abdominal distension. The clinical examination showed pleural effusion, ascites and an enlarged axillary lymph node on the right side. In gynecological sonography ascites, an ovarian cyst and peritoneal carcinosis in the pouch of Douglas were detected, which were potentially indicative of ovarian cancer. A staging laparoscopy was performed to confirm the diagnosis of ovarian cancer and to evaluate operability. Intraoperatively white milky ascites, white-yellow marbling of the liver and white stipple bedding on the diaphragm and liver were detected. The ovaries and the fallopian tubes were tumorously enlarged. Biopsies were taken from the right fimbrial funnel, the liver around the falciform ligament and the diaphragm. Histology of all abdominal biopsies and the axillary lymph node revealed high lymphatic infiltration matching a stage III B-cell-lymphoma. The patient was transferred to the hemato-oncological department for further therapy. Six cycles of cytostatic therapy with R-CHOP (rituximab, cyclophosphamide, hydroxydaunorubicin, vincristine sulfate, prednisone) were initiated. The patient is doing well and in stable disease 6 months after completion of cytotoxic therapy. This case report presents a rare case of manifestation of an extra nodal B-cell-lymphoma with abdominal presentation that mimicked ovarian cancer.